Structural, morphological and magnetic characterization of Sm-substituted Ni-Zn ferrite - Zahari, M.H.B. (Bentham Science Publishers, 2020)
Background: Rare earth materials are known for its salient electrical insulation properties with high values of electrical resistivity. It is expected that the substitution of rare earth ions into spi-nel ferrites could significantly alter its magnetic properties. In this work, the effect of the addition of Samarium ions on the structural, morphological and magnetic properties of Ni0.5Zn0.5SmxFe2-xO4 (x=0.00, 0.02, 0.04, 0.06, 0.08, 0.10) synthesized using sol-gel auto combustion technique was inves-tigated. Methods: A series of Samarium-substituted Ni-Zn ferrite nanoparticles (Ni0.5Zn0.5SmxFe2-xO4 where x=0.00, 0.02, 0.04, 0.06, 0.08, 0.10) were synthesized by sol-gel auto-combustion technique. Structur-al, morphological and magnetic properties of the samples were examined through X-Ray Diffraction (XRD), Field-Emission Scanning Electron Microscope (FESEM) and Vibrating Sample Magnetometer (VSM) measurements. Results: XRD patterns revealed single-phased samples with spinel cubic structure up to x= 0.04. The average crystallite size of the samples varied in the range of 41.8 â 85.6 nm. The prepared samples exhibited agglomerated particles with larger grain size observed in Sm-substituted Ni-Zn ferrite as compared to the unsubstituted sample. The prepared samples exhibited typical soft magnetic behavior as evidenced by the small coercivity field. The magnetic saturation, Ms values decreased as the Sm3+ concentration increases. Conclusion: The substituted Ni-Zn ferrites form agglomerated particles inching towards more uniform microstructure with each increase in Sm3+ substitution. The saturation magnetization of substituted samples decreases with the increase of samarium ion concentration. The decrease in saturation magnetization can be explained based on weak super exchange interaction between A and B sites. The difference in magnetic properties between the samples despite the slight difference in Sm3+ concentra-tions suggests that the properties of the NiZnFe2O4 can be âtunedâ, depending on the present need, through the substitution of Fe3+ with rare earth ions. Â© 2020 Bentham Science Publishers.